2019
DOI: 10.1038/s41467-019-09683-z
|View full text |Cite
|
Sign up to set email alerts
|

CXCL4 assembles DNA into liquid crystalline complexes to amplify TLR9-mediated interferon-α production in systemic sclerosis

Abstract: Systemic sclerosis (SSc) is a chronic autoimmune disease characterized by fibrosis and vasculopathy. CXCL4 represents an early serum biomarker of severe SSc and likely contributes to inflammation via chemokine signaling pathways, but the exact role of CXCL4 in SSc pathogenesis is unclear. Here, we elucidate an unanticipated mechanism for CXCL4-mediated immune amplification in SSc, in which CXCL4 organizes “self” and microbial DNA into liquid crystalline immune complexes that amplify TLR9-mediated plasmacytoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
158
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(168 citation statements)
references
References 63 publications
(147 reference statements)
9
158
0
1
Order By: Relevance
“…Methods used for SAXS experiments and data fitting were based around those that have been previously described 30,[33][34]55 .…”
Section: Saxs Experiments With Model Membranesmentioning
confidence: 99%
“…Methods used for SAXS experiments and data fitting were based around those that have been previously described 30,[33][34]55 .…”
Section: Saxs Experiments With Model Membranesmentioning
confidence: 99%
“…The possible pathobiological role of CXCL4 in brosis of SSc was highly proved in the previous studies [12,54,55]. For example, serum CXCL4 levels were signi cantly increased in SSc and served as a marker of lung brosis [10].…”
Section: Discussionmentioning
confidence: 90%
“…It was also reported that CXCL4 can directly bind to the CXCR3B chemokine receptor isoform or lipoprotein-related protein-1(LRP1) [11]. In patients with SSc, CXCL4 binds DNA into speci c immune complexes that magnify plasmacytoid dendritic cell (pDC) -hyperactivation and produce in ammatory cytokines, which independent of CXCR3 [12]. These data suggest the involvement of CXCL4…”
Section: Introductionmentioning
confidence: 92%
“…PF4 binds to and aggregates polyanions like heparin 26 . We and others have found that PF4 similarly aggregates NETs, physically compacting them, and enhancing their resistance to endogenous and microbial nucleases 27,28 . We speculated that this activity may be, in part, responsible for our previous observation that PF4 enhances survival in murine lipopolysaccharide (LPS) endotoxemia 29 .…”
Section: Introductionmentioning
confidence: 77%
“…In studies designed to investigate the role of neutrophils in the prothrombotic nature of HIT, we observed that PF4, a chemokine known to cross-aggregate polyanions like heparin 26 , also binds to NETs, presumably via the polyanionic backbone of their DNA, causing them to become physically compact. It has recently been shown that PF4-cfDNA complexes form in vivo during systemic sclerosis 28 and it is likely that they also occur during conditions such as sepsis that precipitate both NETosis and platelet degranulation 22 . We have recently shown that PF4 binding enhances NET resistance to lysis by DNase I and microbial nucleases without displacing histones 27 .…”
Section: Discussionmentioning
confidence: 99%